Coupled superconductors and beyond - Josephson, Brian D. (Физика низких температур, 2012)
This paper describes the events leading to the discovery of coupled superconductors, the author’s move in the
1970s to a perspective where mind plays a role comparable to matter, and the remarkable hostility sometimes
encountered by those who venture into unconventional areas.